Sistema de produção orgânico de milho (Zea mays L.), feijão (Phaseolus vulgaris L.) e mandioca (Manihot esculenta Crantz) consorciados com soqueira de cana-de-açúcar (Sacharum spp.) - Apolari, João Paulo (2009)
Greater stability of an agroecosystem can be achieved through the consortium system under organic management, becomes an important environmental factor to a highest stability of the agroecosystem. The objective was to study a system of production for organic crops of maize (Zea mays L., cv. BR 106), bean (Phaseolus vulgaris L., cultivar IAC Pérola) and manioc (Manihot esculenta CRANTZ, cv. IAC 15), intercropped with ratoon-cane (Saccharum spp.). The experimental design was a randomized, with eight (8) treatments and four (4) replicates, as follows: T1 ratoon-cane without intercropping (control), T2: ratooncane and intercropping of maize (cs + mi), T3: ratoon-cane and intercropping of bean (cs + fe); T4: ratoon-cane and intercropping of manioc (cs + ma), T5: ratooncane and intercrops of maize and bean (cs + mi + fe) T6: ratoon-cane and intercrops of maize and manioc (cs + mi + ma); T7 ratoon-cane and intercrops of bean and manioc (cs + f + ma), T8: ratoon-cane and intercrops of maize, bean and manioc (cs + mi + fe + ma). Productivity of the crops, the gross income obtained and the residual biomass waste of maize, beans and manioc, in each system were evaluated. For the conditions of the experiment, the treatment intercropping maize (T2) showed the best results on productivity of green maize ears (kg/ha), production of biomass (kg/ha) and gross income (R$/ha). The alternative of the consortium of distinct crops with ratoon-cane proves to be an effective technique that, from the viewpoint of agroecology, becomes an important tool for preserving and maintaining the agroecosystem, besides providing alternative foods and additional income to the farmer.